2022
DOI: 10.3389/fpsyg.2022.871254
|View full text |Cite
|
Sign up to set email alerts
|

Patient reported quality of life in young adults with sarcoma receiving care at a sarcoma center

Abstract: BackgroundSarcomas are a diverse group of neoplasms that vary greatly in clinical presentation and responsiveness to treatment. Given the differences in the sites of involvement, rarity, and treatment modality, a multidisciplinary approach is required. Previous literature suggests patients with sarcoma suffer from poorer quality of life (QoL) especially physical and functional wellbeing. Adolescent and young adult (AYA) patients are an underrepresented population in cancer research and have differing factors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…When compared with previous studies, [ 3 , 12 ] sarcoma survivors in our study had higher global QOL mean scores. A recent study in the United States showed that young adults with sarcoma had lower QOL than the general population [ 13 ]. Among functioning scales, emotional and social functioning had the lowest mean scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared with previous studies, [ 3 , 12 ] sarcoma survivors in our study had higher global QOL mean scores. A recent study in the United States showed that young adults with sarcoma had lower QOL than the general population [ 13 ]. Among functioning scales, emotional and social functioning had the lowest mean scores.…”
Section: Discussionmentioning
confidence: 99%
“…Tool IV consisted of a MMSE, [11] a 30-point test designed to measure cognitive impairment among sarcoma survivors and classified as normal cognition (> 24), mild cognitive impairment [19][20][21][22][23], moderate impairment [10][11][12][13][14][15][16][17][18], and severe cognitive impairment (<9).…”
Section: Tool Iv: Mmsementioning
confidence: 99%